Edge-rich and (N, S)-doped 3D porous graphene as an efficient metal-free electrocatalyst for the oxygen reduction reaction. Issue 93 (20th September 2016) - Wu, Xiaobo; Xie, Zhiyong; Sun, Min; Lei, Ting; Zuo, Zhenmin; Xie, Xiangmin; Liang, Yili; Huang, Qizhong
Abstract : A novel edge-rich and (N, S)-doped 3D porous graphene was synthesized by chemical vapor deposition (CVD) and chemical corrosion. Abstract : A novel edge-rich and (N, S)-doped 3D porous graphene was synthesized by chemical vapor deposition (CVD) and chemical corrosion. The hybrid material as a metal-free electrocatalyst exhibited a four-electron pathway, stronger alkaline tolerance and excellent catalytic activity for oxygen reduction reaction due to the edge effect and heteroatom synergistic effect.